Inclusive Growth, Agriculture and Employment in Nigeria - OLONI, Elizabeth; ASALEYE, Abiola; ABIODUN, Fadeke; ADEYEMI, Opeolu (Journal of Environmental Management and Tourism, 2017)
The Nigerian economy has been experiencing a jobless growth for over two decades. The main driver of this growth has been petroleum oil whose price started falling since 2015. The petroleum oil, which is the major driver of this growth, creates few jobs and as such, it is less inclusive. This paper, therefore, focused on agriculture as alternative to oil and as such investigates the areas where agriculture can replace petroleum oil as the major driver of growth in Nigeria. Majorly, the paper investigates the qualities of agriculture in matching economic growth with reduction in unemployment, inequality and poverty to pave way for inclusive growth within the economy. To achieve the objective above, a secondary data was analyzed using a VAR model which estimated the direct and indirect effects of agriculture on employment, inequality and poverty reduction. The findings revealed that agriculture have negative effects on employment and poverty and positive effects on inequality and gross capital formation. It is therefore, recommended that more emphasis should be placed on adaptation of imported technology to Nigerian’s situation before applying such on agriculture to make it pro-poor growth.